2021
DOI: 10.3390/jcm10194326
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Osteoprotegerin Levels and Severity of Coronary Artery Disease in Patients with Acute Myocardial Infarction

Abstract: Background. Osteoprotegerin (OPG), a glycoprotein of the tumour necrosis factor (TNF) superfamily, is one of the main biomarkers for vascular calcification. Aim. We aimed to evaluate the association between serum OPG levels and extent of coronary lesions in patients with acute myocardial infarction (MI). Methods. Consecutive patients hospitalized for an acute MI who underwent coronary angiography were included. SYNTAX score was calculated to assess the severity of coronary artery disease. The population was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In a prospective study of patients with acute myocardial infarction, Cottin et al announced an association between OPG concentration and the intensity of CAD estimated by the SYNTAX scale. A recent study showed high levels of OPG are independently associated with major damage to the myocardium after ST-elevated myocardial infarction (STEMI) [78]. A recent meta-analysis confirmed that higher levels of OPG are linked to a higher risk of death from all causes and heart disease in people with chronic kidney disease [79][80][81].…”
Section: Discussionmentioning
confidence: 96%
“…In a prospective study of patients with acute myocardial infarction, Cottin et al announced an association between OPG concentration and the intensity of CAD estimated by the SYNTAX scale. A recent study showed high levels of OPG are independently associated with major damage to the myocardium after ST-elevated myocardial infarction (STEMI) [78]. A recent meta-analysis confirmed that higher levels of OPG are linked to a higher risk of death from all causes and heart disease in people with chronic kidney disease [79][80][81].…”
Section: Discussionmentioning
confidence: 96%
“…More than a decade ago, it was observed that the concentration of OPG and OPN in serum was associated with arterial stiffness and the presence and severity of coronary artery disease [13]. Recent articles have proved that high concentrations of OPG and OPN are associated with atherosclerosis-based conditions, such as acute myocardial infarctions [14], peripheral arterial disease (PAD), or other adverse cardiovascular events [15]. The OPN and OPG concentration is higher in symptomatic or unstable atherosclerosis compared to the concentration level in cases of asymptomatic and stable atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…OPG is commonly expressed in bone cells, vascular smooth muscle cells and endothelial cells. It is widely believed that it can be used as a sensitive biomarker of vascular calcification ( 7 ). Considering the rising frequency of CHD and AMI each year, the incidence of these conditions is growing, the mortality and disability rate are also high, and more and more scholars are interested in the causes of CHD and AMI.…”
Section: Discussionmentioning
confidence: 99%
“…MI patients may benefit from the use of bone-related proteins for early risk stratification and prognosis evaluation. In patients with AMI, OPG levels are correlated with the complexity of coronary artery disease(CAD) ( 7 , 8 ). Healthy subjects with low or high coronary artery calcification cannot be distinguished by using OPG.…”
Section: Introductionmentioning
confidence: 99%